ИНСТИТУЦИОНАЛЬНЫЕ АСПЕКТЫ ПОВЫШЕНИЯ КЛИЕНТООРИЕНТИРОВАННОСТИ В ГОСУДАРСТВЕННОМ УПРАВЛЕНИИ - E. M. Mukhametkalieva (Экономика: стратегия и практика, 2018)
The article examines the institutional aspects of improving the customer focus of public administration. The author suggests improving the system of public administration within one of the most important modern principles of quality management-customer focus. Currently public administration in Kazakhstan is in the process of transformation into a client-oriented government, the purpose of which is to focus on the desires, expectations and needs of citizens and their consideration in the course of the activities of public authorities. In turn, it is the legislation that creates specific conditions or restrictions that must be met in order to achieve the objectives of public administration. In this regard, the institutional aspect of increasing customer focus in public administration, including in the process of providing public services is its legal framework. In turn, the improvement of any legislative act will be preceded by the initiation of the bill, which occurred in a timely and in the right context.In this regard, the author as one of the ways to increase customer focus in public administration proposes to grant the right of legislative initiative to the Supreme Court. Since the judicial authorities with extensive experience in judicial practice and are most quickly able to respond to the growing needs and demands of society, which is the basis of the concept of client-oriented state.